Evaluation of factors responsible for dynamics of direct costs of building elements in cross-river state, Nigeria - Ujene, A.O.; Achuenu, E. (Penerbit UKM, 2013)
The difficulty in accurately forecasting costs of building projects is traceable to inability to determine the nature and causes of variation in direct costs. This study evaluates the severity of the impact of eighty factors responsible for the dynamics of direct cost of building elements in Cross River State of Nigeria. The objective is to compare consultants and contractors perception of the severity of the factors on differential in direct costs. To achieve this objective, a field survey involving a sample of 91 contractors and 46 consultants was conducted. Data were collected with the aid of structured questionnaires and analysed using mean item score, and Mann-Whitney U test. The results reveal that fifteen factors have very high significant effect on the dynamics of direct costs (MS ≥ 4.20) from environmental, macro-economic and construction related factors. There is also high agreement between contractors and consultants’ perception of the influence of the factors (P=0.801). It is recommended that stakeholders should give adequate priority to site conditions, method of construction, macroeconomic indices and cost control mechanism through effective planning, cost recording and cost analysis in their effort to accurately forecast cost of projects.